Influence of Remote Auditing, CAATs, and Professional Skepticism on Audit Quality : A Central Java Case - Vicky Pratama Mahardika; Edy Supriyono; Nurmadi Harsa Sumarta (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to find empirical evidence regarding the influence of remote audits, Computer Assisted Audit Techniques, and Professional Skepticism on Audit Quality. This study utilizes a survey method by distributing questionnaires to auditors working for the Central Java Provincial Representative Audit Board (BPK). The sample was determined using the Slovin formula with a 10% error tolerance rate, resulting in 67 sample from 199 population. A probability sampling method with a simple random sampling procedure was applied to ensure equal selection opportunities. Data analysis was conducted using a descriptive statistical approach in IBM SPSS version 27. The results evidence that remote audit has a significant and positive impact on audit quality. Similarly, CAATs and professional skepticism also significantly and positively affect audit quality. Moreover, these three variables collectively influence audit quality. The findings of this study provide insights for audit institutions to enhance audit quality by adopting remote auditing, utilizing CAATs, and fostering professional skepticism among auditors. This study contributes to the literature by empirically examining the simultaneous impact of remote auditing, CAATs, and professional skepticism on audit quality, particularly in the context of government audits in Indonesia.